Joint instability leads to long-term alterations to knee synovium and osteoarthritis in a rabbit model. Issue 6 (June 2016) - Egloff, C.; Hart, D.A.; Hewitt, C.; Vavken, P.; Valderrabano, V.; Herzog, W.
Summary: Objectives: Joint instability is believed to promote early osteoarthritic changes in the knee. Inflammatory reactions are associated with cartilage degradation in osteoarthritis (OA) but their possible synergistic or additive effects remain largely unexplored. The goal of the present study was to investigate the in vivo effects of Botulinum Toxin A (BTX-A) induced joint instability on intraarticular alterations in an otherwise intact rabbit knee joint model. Methods: Ten 1-year-old female New Zealand White rabbits (average 5.7 kg, range 4.8–6.6 kg) were randomly assigned to receive three monthly unilateral intramuscular injections of BTX-A (experimental group), or no treatment (control group). After 90 days, all knees were analyzed for specific mRNA levels using RT-qPCR. The synovium and cartilage tissue was assessed for histological alterations using the OARSI scoring system. Results: Cartilage and synovial histology showed significant higher OARSI scores in the BTX-A group animals compared to the untreated controls and contralateral limbs. There were no differences between the untreated control and the contralateral experimental limbs. Gene expression showed significant elevations for collagen I, collagen III, nitric oxide, TGF-β, IL-1 and IL-6 compared to the healthy controls. Conclusion: BTX-A induced joint instability in a muscle weakness model uniquely leads to alterations in gene expression and histological changes in the synovial membranes and cartilage in otherwise intact knee joints. These results lead to the conclusion that joint instability may promote an inflammatory intraarticular milieu, thereby contributing to the development of OA.